1993
DOI: 10.1016/0014-5793(93)80510-2
|View full text |Cite
|
Sign up to set email alerts
|

Triple helix formation at A8XA8·T8YT8

Abstract: We have examined the formation of DNA triple he&es between the oligonucleotides T,XTs (X = A,C,G,T) and DNA fragments containing the target sequences A,XA,.T,YT, (X=T,C,G; Y=A,G,C), by DNase I footprinting. We find that A8GA8-T&T* yields a footprint with T&T8 and shows a weaker interaction with T,, and T,GTB. AsC&*T,GT, yields a footprint with T,,, and shows weaker interaction with T,CTs. &TAs.T,AT, yields a footprint with T,GT, and shows weaker interaction with T,,. Each of the successful complexes is charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 12 publications
(4 reference statements)
4
31
2
Order By: Relevance
“…Before discussion of the effect of various central triplet combinations on the antiparallel triplexes studied in this paper, it should be noted that all the oligonucleotides produce footprints at each target at concentrations of 10 µM, and many complexes are still stable at 1.0-3.0 µM, even for those containing non-standard central triplets. This is in marked contrast to the results for parallel triple helix formation at A 8 XA 8 sites using T 8 XT 8 oligonucleotides which showed that a mismatch in the center of the third strand could totally abolish triplex formation, even at oligonucleotide concentrations as high as 100 µM (Chandler & Fox, 1993). This lower stringency and tighter binding could be a general property of antiparallel triplexes, but may reflect the greater stability of the antiparallel G‚-GC over parallel T‚AT triplets.…”
Section: Discussioncontrasting
confidence: 82%
“…Before discussion of the effect of various central triplet combinations on the antiparallel triplexes studied in this paper, it should be noted that all the oligonucleotides produce footprints at each target at concentrations of 10 µM, and many complexes are still stable at 1.0-3.0 µM, even for those containing non-standard central triplets. This is in marked contrast to the results for parallel triple helix formation at A 8 XA 8 sites using T 8 XT 8 oligonucleotides which showed that a mismatch in the center of the third strand could totally abolish triplex formation, even at oligonucleotide concentrations as high as 100 µM (Chandler & Fox, 1993). This lower stringency and tighter binding could be a general property of antiparallel triplexes, but may reflect the greater stability of the antiparallel G‚-GC over parallel T‚AT triplets.…”
Section: Discussioncontrasting
confidence: 82%
“…We have recognized the single thymine that interrupts the block of purines with guanine, forming a G:TA triplet. The formation of G:TA triplets has been described by several groups [23][24][25][26], though it is thought to be less stable than T:AT and C + :GC. In addition we have changed the central thymine to adenine, by sitedirected mutagenesis, generating a perfect homopurine sequence GAGAAAAAAGAA [tyrT(46A)], targeting this with the oligonucleotide CTCTTTTTTCTT (12T), forming a structure containing 9iT:AT and 3iC + :GC triplets.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly recognition is generally limited to the duplex purine strand, so that triplexes can only be formed at homopurine.homopyrimidine sequences. Recent work has demonstrated that, within the parallel motit, it is also possible to form G'TA [6][7][8][9][10][11][12][13][14] and T-CG [7,8,15] triplets, although these each contain only one hydrogen bond and are thought to be less stable than T. AT and C ÷. GC.…”
Section: Introductionmentioning
confidence: 99%